3-79w=-4

Combine w and 79.

3-w⋅79=-4

Move 7 to the left of w.

3-7w9=-4

3-7w9=-4

Subtract 3 from both sides of the equation.

-7w9=-4-3

Subtract 3 from -4.

-7w9=-7

-7w9=-7

Multiply both sides of the equation by -97.

-97⋅(-7w9)=-97⋅-7

Simplify -97⋅(-7w9).

Cancel the common factor of 9.

Move the leading negative in -97 into the numerator.

-97⋅(-7w9)=-97⋅-7

Move the leading negative in -7w9 into the numerator.

-97⋅-7w9=-97⋅-7

Factor 9 out of -9.

9(-1)7⋅-7w9=-97⋅-7

Cancel the common factor.

9⋅-17⋅-7w9=-97⋅-7

Rewrite the expression.

-17⋅(-7w)=-97⋅-7

-17⋅(-7w)=-97⋅-7

Cancel the common factor of 7.

Factor 7 out of -7w.

-17⋅(7(-w))=-97⋅-7

Cancel the common factor.

-17⋅(7(-w))=-97⋅-7

Rewrite the expression.

-1⋅(-w)=-97⋅-7

-1⋅(-w)=-97⋅-7

Multiply.

Multiply -1 by -1.

1⋅w=-97⋅-7

Multiply w by 1.

w=-97⋅-7

w=-97⋅-7

w=-97⋅-7

Simplify -97⋅-7.

Cancel the common factor of 7.

Move the leading negative in -97 into the numerator.

w=-97⋅-7

Factor 7 out of -7.

w=-97⋅(7(-1))

Cancel the common factor.

w=-97⋅(7⋅-1)

Rewrite the expression.

w=-9⋅-1

w=-9⋅-1

Multiply -9 by -1.

w=9

w=9

w=9

Solve for w 3-7/9w=-4